Equatorial water waves with underlying currents in the f-plane approximation. Issue 11 (18th August 2018) - Kluczek, Mateusz
Abstract: We present an exact solution to the governing equations for equatorial geophysical water waves which admit a constant underlying zonal current and a variable meridional current in the f -plane approximation. The solution is three-dimensional, nonlinear and explicit in Lagrangian formulation. We provide an analysis of the mean flow velocities and the related mass transport.